Navigating the world of deepfake technology - Kumar, Pawan; Lakhera, Girish; Ozen, Ercan; Taneja, Sanjay (IGI Global, 2024)
The digital age has ushered in an era of incredible innovation, but it's also opened the door to new threats. Deepfakes, hyper-realistic manipulated videos and images, are blurring the lines between truth and fiction. Malicious actors can use deepfakes to create fake news that sways elections, fabricate celebrity scandals to damage reputations, or even launch targeted attacks against businesses. This loss of trust can have a devastating impact on individuals, society as a whole, and especially organizations struggling to maintain brand integrity and secure operations.Navigating the World of Deepfake Technology equips you to understand deepfakes, from their work to the legal issues surrounding them. It also provides practical strategies to identify deepfakes and mitigate their risks, empowering you to protect yourself and your organization. Whether you're a business leader, journalist, or simply someone concerned about the impact of deepfakes, this book is essential reading. It's your key to staying informed and safeguarding yourself in a world increasingly reliant on digital media.
Keywords: Artificial intelligence; Artificial intelligence -- Social aspects; Disinformation; Expert systems (Computer science); Human-computer interaction; Machine learning; Social media -- Political aspects